2015
DOI: 10.5137/1019-5149.jtn.15177-15.2
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of traumatic acute subdural hematomas: outcomes and predictive factors in a single center experience

Abstract: ASDH is associated with high mortality. GCS score and the thickness of the ASDH are important predictors of mortality. Age, additional trauma, and interval between trauma and hospital admission are major predictive factors for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 9 publications
4
29
0
6
Order By: Relevance
“…Many studies stated that the outcome of severe head injury patients with ASDH was mostly poor but with a percentage of a good outcome [3,4,[7][8][9]. These studies stated the overall outcome of all the severe head injury patients without subgrouping analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies stated that the outcome of severe head injury patients with ASDH was mostly poor but with a percentage of a good outcome [3,4,[7][8][9]. These studies stated the overall outcome of all the severe head injury patients without subgrouping analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, traumatic acute subdural hematoma (ASDH) results in high mortality despite intensive treatment [1,2]. It is commonly associated with brain edema, subarachnoid hemorrhage, brain contusions, and diffuse axonal injury, and all affect the neurological outcome [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Previous studies have reported that the mortality rate was higher in patients with ASDH with lower Glasgow Coma Scale (GCS) scores, a greater hematoma thickness, an excessive midline shift, and in those who were younger. [1,[8][9][10] Furthermore, some studies indicate a higher mortality rate in patients with additional traumatic lesions, particularly in those having experienced out-of-vehicle traffic accidents. [8,11,12] Although DC has become more popular in recent years, its use has not been generally accepted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Acute subdural hematoma (ASDH) is a major clinical entity in traumatic brain injury (TBI) and is diagnosed by computed tomography (CT) as a hyperdense, extra-axial, crescent lesion between the dura and brain parenchyma 1) . The acceleration-deceleration force applied during traumatic insults can result in stretching and tearing of the cross-linking blood vessels and cortical arteries, which is the source of hematoma formation [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…The pressure imposed on the cerebral tissue by a hematoma is not the only factor that affects neurological outcomes, because ASDH is commonly associated with brain edema, contusions, and diffuse axonal injury (DAI) 1,6,7) . This can increase midline shift (MLS) and make hematoma removal inappropriate for satisfactory patient outcomes 8,9) .…”
Section: Introductionmentioning
confidence: 99%